1993
DOI: 10.1063/1.109207
|View full text |Cite
|
Sign up to set email alerts
|

Metal contacts to gallium nitride

Abstract: Gallium nitride metal-semiconductor-metal photodetectors prepared on silicon substrates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
162
2
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(172 citation statements)
references
References 13 publications
6
162
2
2
Order By: Relevance
“…Kurtin et al [32] suggested that the Schottky barrier height on GaN should depend directly on the work function or electronegativity difference between the metal electrode and GaN. Foresi and Moustakas [33] observed this direct correlation experimentally, while Guo et al [34] and Mori et al [35] observed only a weak dependence of the Schottky barrier height on the metal work function for n-type GaN and p-type GaN, respectively. The 1998 review of metal-GaN contact technology by Liu and Lau [19] reported that, for a variety of contact metals with both low and high work functions, Schottky barrier heights at the metal-GaN interface varied with metal work function, within the experimental scatter.…”
Section: Introductionmentioning
confidence: 85%
“…Kurtin et al [32] suggested that the Schottky barrier height on GaN should depend directly on the work function or electronegativity difference between the metal electrode and GaN. Foresi and Moustakas [33] observed this direct correlation experimentally, while Guo et al [34] and Mori et al [35] observed only a weak dependence of the Schottky barrier height on the metal work function for n-type GaN and p-type GaN, respectively. The 1998 review of metal-GaN contact technology by Liu and Lau [19] reported that, for a variety of contact metals with both low and high work functions, Schottky barrier heights at the metal-GaN interface varied with metal work function, within the experimental scatter.…”
Section: Introductionmentioning
confidence: 85%
“…Compared to other III-V semiconductors, the strong ionic bonding of III-nitrides, due to the large difference in electro-negativity between group III elements and N, suppresses the formation of surface states within the fundamental energy gap. 44,45 Moreover, the MBE grown III-nitride nanowires generally possess N-polarity, which are more stable that their Ga-polarity counterpart in harsh photocatalysis conditions. The balanced surface redox reactions, due to the optimized surface electronic properties with controlled Mg dopant incorporation, also contribute to the enhanced stability.…”
mentioning
confidence: 99%
“…The p-, i-and n-a-Si:H layers, with a total thickness of 288 nm, were deposited by a plasma-enhanced chemical vapor deposition. The contact resistance between back contact and GAZO was measured using the transmission line model (TLM) method [15][16][17]. The optical reflectance of the films was measured with an ultraviolet-visible spectrophotometer (UV-VIS, Hong-Ming Technology Co., Ltd., Taipei, Taiwan).…”
Section: Methodsmentioning
confidence: 99%